Adsorption of Aromatic Sulphonic Acids onto Macroporous Exchangers: Effect of the Chemical Structure of the Adsorbent on the Adsorption Capacity - Long Chao; Zhang Quanxing; Chen Jinlong (Adsorption Science & Technology)
The adsorption of 2-naphthalene sulphonic acid from aqueous solution was studied using macroporous weak base exchangers with different matrices. This study reports the results of the favourable adsorption behaviour of 2-naphthalene sulphonic acid onto polymeric anion exchangers. The difference in adsorption affinity, together with the enthalpic and entropic changes associated with the adsorption process, was interpreted in terms of the chemical structure of the exchangers and appropriate interaction between the non-polar moiety of the aromatic anion and the exchanger matrices. The exchanger matrix had a distinct influence on the adsorption capacity of the aromatic sulphonic acid.